Designing an Instructional Module for Classroom Teaching Based on the Multiple Intelligences Theory - Malapad, Lee P.; Quimbo, Maria Anna T. (Philippine social science journal (University of Negros Occidental-Recoletos- Online), 2021)
Lesson content needs active engagement to excite student interest. Teachers face challenges on student engagement in classroom teaching where learning has become procedural. This field study developed an instructional module integrating the 5Es method of instruction anchored on Howard Gardner’s Theory of Multiple Intelligences. Chislett’s multiple intelligence (MI) test was administered to Grade 7 students and the Science teacher for learning needs assessment determining their dominant multiple intelligences. The dominant MI of the students determined the enrichment activities incorporated in the 5E-MI instructional module and teaching method. During implementation, the teacher and the students were observed to assess the perceived usefulness of the module. The study established that the 5E-MI instruction module was a useful lesson planning method to increase students' engagement, who were observed to be attentive and participative during the implementation. Lesson planning was easier for the teacher since enrichment activities incorporated were guided by the dominant MI of the students. Through this study, educators are provided direction in incorporating MI in lesson planning and curriculum integration.